And My Immigrant Ship Sails On: Returning on Deck with Ricci’s Lives of the Saints Trilogy - Niccoli, Gabriel (Italian Canadiana)

(untitled) (Iter Press, 2021)
This article addresses the theme of nostos and of immigrant journeying by locating the author and his memories on the very liner Saturnia that brought, in an eerily fanciful quirk of fate, Ricci’s young protagonist and his mother to Canada. The writer frames his reading of Ricci’s Lives of the Saints with a testimonial to the authenticity of the world the novel evokes, the world of the author’s own childhood and adolescence. The essay that follows traces the convergent lines of critical insight, memory and the imagination.